Forever home - Ayoub, Jenna (Kaboom!, 2021)
"Willow's nomadic childhood takes a surprising turn as her military parents bring her to the historic Hadleigh House, where her chances of finding her permanent home aren't looking good when she meets some unexpected occupants--GHOSTS!"--